A brief review of genus Catopta Staudinger, 1899 (Lepidoptera: Cossidae) with description of a new species from China - Yakovlev, Roman V.; Saldaitis, Aidas; Kons, Hugo Jr.; Borth, Robert (Zootaxa, 2013)
A checklist of the genus Catopta Staudinger, 1889 is presented. A new species, С. dusii sp. nov., from the Xiling Xue Shan Mountains of in the Noth West China’s Sichuan Province is described.